Management of Consumers Embraces Drone Delivery (Marketing i Menedžment Innovacij)
Over the past few years, significant progress has been made in the field of drone technology, leading to its implementation and transformation in various industries. As technology has improved, drones have become increasingly adaptable to numerous tasks, such as delivering packages right to customers' front doors. As the need for swift and reliable delivery options increases, drone delivery is an option that businesses and consumers alike should consider. This paper studies the underlying factors that influence consumers' intentions to adopt drone delivery services in Portugal. A quantitative methodology was used, and 155 responses were collected from Portuguese citizens. The findings indicate that perceived usefulness, perceived privacy risk, and attitudes serve as key predictors of user behavioural intentions among individuals in Portugal. Moreover, they highlight that perceived usefulness and perceived privacy risks exert an indirect influence on behavioural intentions through attitudes. Consequently, the comprehensive analysis underscores the significant impact of perceived usefulness on behavioural intentions, with attitudes and perceived privacy risks closely behind. The study uncovers new insights into consumer adoption of drone delivery services. This finding suggests that promoting the advantages of drone technology, emphasising its usefulness, efficiency, and convenience in advertising, can positively impact consumer perception and willingness to adopt. Furthermore, this study indicates that addressing potential consumer concerns about drone delivery, such as privacy, safety, and reliability, is essential. Clear communication about the measures taken to ensure these aspects can mitigate apprehensions and enhance acceptance. Governments play a crucial role in regulating drones to increase trust, protect users, and promote a favourable environment for adoption. Public awareness campaigns led by governments can educate citizens about the benefits and safe use of drones. Transparent communication about regulatory measures, safety features, and the positive impacts of drone technology on society can demystify drones and build public trust.